Implementation of Precast Concrete Technology in Type 36 Residential Building Construction Natural Disaster Relocation - Sahoa, Riandy; Corneles, Marceline; Prasetyo, Teguh; Watugigir, Novia; Rumbayan, Rilya; Peginusa, Stefani S (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Manado, 2023)
Currently, natural disasters such as landslides and floods occur everywhere. The government is trying to overcome the impact of this natural disaster by building natural disaster relocation housing. In conditions like these, fast, cheap and environmentally friendly construction is needed. One of the technologies currently developing in the world of construction is precast concrete which has advantages in terms of cost and implementation time. One of the precast concrete technologies is the Instant Panel System Superior House (RUSPIN) method. RUSPIN is a precast house frame technology with a panel system using bolted connections. This research was conducted to overcome problems for people affected by natural disasters who need housing that can be built quickly and relatively cheaply. The aim of this research is to design, calculate the costs and time required to build type 36 disaster relocation housing using RUSPIN technology. This research method uses a computer laboratory. Where to design and create working drawings using Skectup and Autocad software. After that, calculate the costs and time needed to build this house. The results of this research are a type 36 house design with a construction cost of Rp. 194,143,000.00 with a time required of 2 months. So RUSPIN technology is suitable for disaster relocation housing because of the relatively low cost and fast construction time.